The Use of UNO Card Game in Learning Arabic and Its Influence on Students' Ability in fahm al-Maqru' - Nurhalimah, Siti; Ahmad, Hishomudin (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This research is based on the problems of students learning Arabic. Some students do not pay much attention to the subject matter delivered by the teacher, and they do not understand the Arabic text they read. This leads to their low Arabic language skills. Looking at student learning outcomes, only 30% get scores above the Minimum Completeness Criteria (KKM), and 70% do not reach the predetermined KKM limit. Based on the results of observations made by researchers in the field, namely Madrasah Ibtidaiyah Az Zahra Bandung, Arabic learning media used by teachers is still not adequate, especially in improving the ability of fahm al-maqru' students. This study aimed to determine the effect of using UNO card game learning media on the ability of fahm al-maqru’ students. The method used in this study is quasi-experimental. The approach used is quantitative. Observation, interviews, and tests were carried out as the data collection method in this study. As for processing research data, researchers used SPSS V. 22. The result of this study was that the student fahm al-maqru's ability score before using UNO card game media reached an average score of 65.5, and after using the media, the average value of students' fahm al-maqru’ ability reached 83.5. Thus, it can be concluded that using UNO card game media affects the ability of fahm al-maqru' students.